2017
DOI: 10.1007/s10880-017-9510-2
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Disparities, Treatment Engagement, and Attrition Among Racial/Ethnic Minorities with Severe Mental Illness: A Review

Abstract: Mounting evidence indicates that there are mental health disparities in the United States that disadvantage racial/ethnic minorities in medical and mental health settings. Less is known, however, about how these findings apply to a particularly vulnerable population, individuals with severe mental illness (SMI). The aim of this paper is to (1) provide a critical review of the literature on racial/ethnic disparities in mental health care among individuals with SMI; (2) identify factors which may contribute to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
116
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(121 citation statements)
references
References 118 publications
3
116
1
1
Order By: Relevance
“…34 Although little evidence exists to suggest that traditional healers change the course of SMI, individuals with SMI may commonly seek help from traditional/spiritual healers as a means to cope with their illness, which may delay taking medication. 35,36 The decrease of the rates of ever having been treated with traditional Chinese medicine or by traditional/spiritual healers from 1994 to 2015 may be related to the increase in knowledge about mental illness, the availability of mental health facilities and the change in help-seeking behaviour with socioeconomic development. 7,21…”
Section: Discussionmentioning
confidence: 99%
“…34 Although little evidence exists to suggest that traditional healers change the course of SMI, individuals with SMI may commonly seek help from traditional/spiritual healers as a means to cope with their illness, which may delay taking medication. 35,36 The decrease of the rates of ever having been treated with traditional Chinese medicine or by traditional/spiritual healers from 1994 to 2015 may be related to the increase in knowledge about mental illness, the availability of mental health facilities and the change in help-seeking behaviour with socioeconomic development. 7,21…”
Section: Discussionmentioning
confidence: 99%
“…Further, this review did not adequately address the risk factor of race and ethnicity. Although research indicated that White/Caucasian ethnicity was a risk factor for disordered eating behaviors among the LGBT subgroups, it should also be recognized that historically, there has been a racial disparity in access to mental health care, with racial minorities being less likely to seek treatment for mental health (i.e., [ 114 ]). Therefore, future research should assess whether racial identity is truly a risk factor, or if the difference in rates of disordered eating behaviors may be due to lack of access to the necessary mental health care.…”
Section: General Conclusionmentioning
confidence: 99%
“…45 We were not able to address whether individuals with a poorer illness course were more delayed in receiving treatment. Furthermore, racial/ethnic disparities in mental health access and treatment 46 and in the success of treatments 47 may have contributed to the observation that minority individuals had a poorer course of illness. Increasing access to early intervention is especially critical for individuals with demographic and symptomatic/ illness profiles that bode poorly for long-term outcome.…”
Section: Discussionmentioning
confidence: 99%